Thermal and light induced polymorphism in iron(II) spin crossover compounds. - Thompson, A; Goeta, A; Real, J; Galet, A; Carmen Munoz, M (2004)
The spin crossover complexes [Fe[H(2)B(pz)(2)](2)L]([H(2)B(pz)(2)](-)= dihydrobis(pyrazolyl)borate, L = 2,2[prime or minute]-bipyridine (1), bipy and 1,10-phenanthroline, phen (2)) undergo both thermal and light induced spin crossover, but the structure of the low spin and light induced high spin states for are different from that of the thermally induced high spin state and from those of.